2012
DOI: 10.1016/j.neuint.2012.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Guanosine protects human neuroblastoma SH-SY5Y cells against mitochondrial oxidative stress by inducing heme oxigenase-1 via PI3K/Akt/GSK-3β pathway

Abstract: Mitochondrial perturbation and oxidative stress are key factors in neuronal vulnerability in several neurodegenerative diseases or during brain ischemia. Here we have investigated the protective mechanism of action of guanosine, the guanine nucleoside, in a human neuroblastoma cell line, SH-SY5Y, subjected to mitochondrial oxidative stress. Blockade of mitochondrial complexes I and V with rotenone plus oligomycin (Rot/oligo) caused a significant decrease in cell viability and an increase in ROS production. Gua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
82
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 62 publications
11
82
0
Order By: Relevance
“…In previous studies from our group, the neuroprotective effect of GUO was shown in hippocampal slices subjected to the OGD/reoxygenation protocol. GUO prevents the decrease in cell viability, by increasing glutamate uptake and glutamine synthetase activity, decreasing glutamate release, ROS production and inflammatory mediators expression, including reduction of iNOS expression [14,15,33,40]. The exact interaction site of GUO in cellular membranes is still unknown, although it has been suggested [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies from our group, the neuroprotective effect of GUO was shown in hippocampal slices subjected to the OGD/reoxygenation protocol. GUO prevents the decrease in cell viability, by increasing glutamate uptake and glutamine synthetase activity, decreasing glutamate release, ROS production and inflammatory mediators expression, including reduction of iNOS expression [14,15,33,40]. The exact interaction site of GUO in cellular membranes is still unknown, although it has been suggested [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…An experimentally based hypothesis is that GUO caused an increase in extracellular ADO levels by competing with nucleoside transporter [19,20]. In fact, some of GUO's neuroprotective effects, but not all, are ADO receptor dependent [18][19][20][21][22]39].…”
Section: Discussionmentioning
confidence: 99%
“…A putative binding site for GUO was already described in rat brain membranes [17], but in opposite, several evidences point to an adenosine (ADO) receptors contribution for GUO effects. Indeed, some, but not all of the observed neuroprotective effects of GUO, were blocked by ADO receptor antagonists, suggesting multiple mechanisms of action for GUO [18][19][20][21][22]. Certainly, GUO effects seem to be directly mediated by action on the brain, as intracerebroventricular or intracortical GUO infusion in experimental models of excitotoxicity have demonstrated neuroprotection [8,13].…”
Section: Introductionmentioning
confidence: 99%
“…Guanosine induces the expression of heme oxygenase 1 (HO1) via the PI3K pathway, thus protecting neural cells [90,91]. This protein acts as a scavenger of NO and has been associated with adaptive cytoprotection against a wide array of toxic insults by modulating antioxidant defenses, such as GSH system and thioredoxin [92,93].…”
Section: Discussionmentioning
confidence: 99%